Cannabis-based product use in a multiple sclerosis cohort. Issue 3 (September 2019) - Schabas, AJ; Vukojevic, V; Taylor, C; Thu, Z; Badyal, A; Chan, JK; Devonshire, V; Traboulsee, A; Sayao, AL; Carruthers, R
Objective: The objective of this study was to characterize the use of cannabis-based products (CBPs) by multiple sclerosis (MS) patients who attend the University of British Columbia Hospital (UBCH) MS clinic. Methods: All patients attending the UBCH MS clinic from January to March 2018 were invited to participate in an anonymous survey that included: patient demographics (sex, age and employment status), self-reported MS-specific data (subtype, disease duration, previous and current disease modifying therapies, symptomatic medications) and CBP use (formulation, frequency, perceived benefits/side-effects). A second cohort of retrospective patient data (CBP use, sex, age, disease subtype and Expanded Disability Status Scale) was extracted from the UBCH MS clinic electronic medical record (EMR). Results: Of 600 surveys distributed, 188 were returned with completed CBP usage. CBP use was daily for 19% ( n = 37), weekly for 6% ( n = 11), monthly for 4% ( n = 7), rarely for 21% ( n = 39) and 50% ( n = 94) never used. Of the CBP users (daily, weekly and monthly), CBP use included: oral ( n = 43/55), smoked/vaporized ( n = 42/55), topical ( n = 14/55) and mucosal ( n = 5/55). EMR data was available for 561 MS patients where cannabis use/non-use was documented. CBP users represented 19% (107/561). Conclusions: CBP use is common based on volunteer reporting, with approximately one out of four patients who attend the UBCH MS clinic using CBPs.